Adpressed tree-fern trunks from the Early Pennsylvanian Joggins Formation of Nova Scotia - Falcon-Lang, Howard (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2005)
Abstract Tree-fern trunks are among the rarest plant fossils in the Early Pennsylvanian Joggins Formation, with only three specimens recorded, all of which are assigned to Artisophyton. Based on trunk dimensions, these fossils are remains of small trees a few metres high. The fades context is known for only one specimen; this tree grew on a well drained, seasonally dry alluvial plain.